1.Упростить выражения:

0 голосов
29 просмотров

1.Упростить выражения:


image

Алгебра (113 баллов) | 29 просмотров
Дан 1 ответ
0 голосов

Объяснение:

5(а^6)*(–3а²b)²= 5(a^6)*9a⁴b²= 45(a^10)b²

{( - {x}^{4} {y}^{3} ) }^{7} \times 8 {x}^{2} {y}^{5} = - {x}^{28} {y}^{21} \times 8 {x}^{2} {y}^{5} = - 8 {x}^{30} {y}^{26}

{( - 0.1 {a}^{2} b{c}^{5} ) }^{2} \times 100b{c }^{4} = 0.01 {a}^{4} {b}^{2} {c}^{ 10} \times 100b{c}^{4} = {a}^{4} {b}^{3} {c}^{14}

- 1 \frac{3}{5} {m}^{4} {n}^{3} \times {( - \frac{1}{2} {m}^{3} {p}^{6} ) }^{3} = - \frac{8}{5} {m}^{4} {n}^{3} \times - \frac{1}{8} {m}^{9} {p}^{18} = \frac{1}{5} {m}^{13} {n}^{3} {p}^{18}

2 \frac{1}{4} {a}^{5} b \times {( \frac{2}{3} a {b}^{3} ) }^{3} = \frac{9}{4} {a}^{5} b \times \frac{8}{27} {a}^{3}{b}^{9} = \frac{2}{3} {a}^{8} {b}^{10}

{( - 5 {a}^{3} {b}^{7} )}^{3} \times {( - \frac{1}{2} {a}^{2} {c}^{6} )}^{2} = - 125 {a}^{9} {b}^{21} \times \frac{1}{4} {a}^{4} {c}^{12} = - \frac{125}{4} {a}^{13} {b}^{21} {c}^{12} = - 31.25{a}^{13} {b}^{21} {c}^{12}.

(2.2k баллов)